Acculturation of Javanese Islam and Mapalus Culture in The Development of Islamic Economic Tradition in Tondano - Hadi, Rahmini; Shafrani, Yoiz Shofwa; Nurhayati, Laily (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Diversity allows the emergence of merging existing cultures into a new culture that does not take away the essence of the previous culture. The success of Tondano Javanese Village in maintaining the existence of economic traditions, especially in the agricultural sector, also plays a role in balancing the economy in the Tondano region. Mapalus is synonymous with the life cycle of the Minahasa community which is closely related to religious values. Development of Javanese Islam in Tondano began to occur after the group of Kiai Mojo and his followers consisting of approximately 60 men, established an association place for them to settle and live there, namely